HII regions in the CALIFA survey: I. Catalog presentation - Espinosa Ponce, Carlos (2020)
We present a new catalogue of H II regions based on the integral field spectroscopy (IFS) data of the extended CALIFA and PISCO samples. The selection of H II regions was based on two assumptions: a clumpy structure with high contrast of H α emission and an underlying stellar population comprising young stars. The catalogue provides the spectroscopic information of 26 408 individual regions corresponding to 924 galaxies, including the flux intensities and equivalent widths of 51 emission lines covering the wavelength range between 3745 and 7200 Å. To our knowledge, this is the largest catalogue of spectroscopic properties of H II regions. We explore a new approach to decontaminate the emission lines from diffuse ionized gas contribution. This diffuse gas correction was estimated to correct every emission line within the considered spectral range. With the catalogue of H II regions corrected, new demarcation lines are proposed for the classical diagnostic diagrams. Finally, we study the properties of the underlying stellar populations of the H II regions. It was found that there is a direct relationship between the ionization conditions on the nebulae and the properties of stellar populations besides the physicals condition on the ionized regions.